2007
DOI: 10.1158/1541-7786.mcr-07-0161
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin-Dependent Kinase Inhibitors Sensitize Tumor Cells to Nutlin-Induced Apoptosis: a Potent Drug Combination

Abstract: Current chemotherapy focuses on the use of genotoxic drugs that may induce general DNA damage in cancer cells but also high levels of toxicity in normal tissues. Nongenotoxic activation of p53 by targeting specific molecular pathways therefore provides an attractive therapeutic strategy in cancers with wild-type p53. Here, we explored the antitumor potential of cyclin-dependent kinase (CDK) inhibitors in combination with a small molecule inhibitor of p53-murine double minute 2 (MDM2) interaction. We show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 60 publications
1
41
0
Order By: Relevance
“…It is possible that MDM2 expression or MDM2 activity are abnormal in LNCaP cells via other means, such as single nucleotide polymorphism of MDM2 (16), or factors affecting Rb kinase activities such as cycling D1 (29), Cdks (30), and p21 (31), all of which have impacts on the outcome of nutlin-3 treatment. In addition, other factors such as MDM4 (17,18), p73 (19) may also contribute to the sensitivity of nutlin-3-induced apoptosis in the absence of amplification of MDM2.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that MDM2 expression or MDM2 activity are abnormal in LNCaP cells via other means, such as single nucleotide polymorphism of MDM2 (16), or factors affecting Rb kinase activities such as cycling D1 (29), Cdks (30), and p21 (31), all of which have impacts on the outcome of nutlin-3 treatment. In addition, other factors such as MDM4 (17,18), p73 (19) may also contribute to the sensitivity of nutlin-3-induced apoptosis in the absence of amplification of MDM2.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, drug combinations involving genotoxic agents (e.g., doxorubicin) have been explored and are found to be synergistic in inducing p53 accumulation and activation of apoptosis. A recent report (Cheok et al 2007) on the combination of CDK inhibitors (Roscovitine and DRB) and nutlin-3 showed a clear synergism in the activation of p53 and apoptosis in p53 wild-type tumor cells. The combination retains the nongenotoxic nature characteristic of the individual compounds.…”
Section: Activation Of P53 Using Combinations Of Drugsmentioning
confidence: 94%
“…Therefore it could be a promising strategy to combine wild type reactivating compounds with those restoring mutant p53 function, such as PRIMA-1 MET /Apr246. Search for the rational combinations of drugs which can produce synergy when combined with Mdm2 inhibitors, revealed that low doses of CDK inhibitors promote apoptosis induction when combined with nutlin [147]. siRNA screen against known human kinases pinpointed to several pathways, including the MAP kinase pathway and the sphingosine kinase pathway whose inhibition may synergize with nutlin [148].…”
Section: Combination Therapymentioning
confidence: 99%